2012
DOI: 10.1103/physrevlett.108.116403
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Polaronic Behavior in the Binary OxidesmHfO2andmZrO2

Abstract: We demonstrate that the three-dimensional (3D) binary monoclinic oxides HfO2 and ZrO2 exhibit quasi-2D polaron localization and conductivity, which results from a small difference in the coordination of two oxygen sublattices in these materials. The transition between a 2D large polaron into a zero-dimensional small polaron state requires overcoming a small energetic barrier. These results demonstrate how a small asymmetry in the lattice structure can determine the qualitative character of polaron localization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
56
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 44 publications
6
56
1
Order By: Relevance
“…The trapping of hole polarons on single O atoms in m-HfO 2 has been previously predicted theoretically [25]. Recent calculations using the cancellation of nonlinearity approach [54] predicted that holes can trap only at 3-coordinated O sites in the bulk of m-HfO 2 [26] with trapping energy of 0.18 eV and with much larger trapping energies at surfaces, featuring two-coordinated O sites.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…The trapping of hole polarons on single O atoms in m-HfO 2 has been previously predicted theoretically [25]. Recent calculations using the cancellation of nonlinearity approach [54] predicted that holes can trap only at 3-coordinated O sites in the bulk of m-HfO 2 [26] with trapping energy of 0.18 eV and with much larger trapping energies at surfaces, featuring two-coordinated O sites.…”
mentioning
confidence: 94%
“…Shallow electron and hole polaron states have been predicted by theoretical calculations in crystalline monoclinic (m)-HfO 2 and m-ZrO 2 [25] and corundum [3]. Subsequent work [26] confirmed that holes can self-trap at three-coordinated O sites in m-HfO 2 and ZrO 2 with …”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Valentin and Selloni described this model for anatase [82] (see also refs [83,84] ) and we have used it extensively in understanding different modifications of TiO2 with nanoclusters [81,[85][86][87] . Figure 7 shows the spin density from the relaxed triplet state for a selection of free and supported TiO2 nanoclusters; ref [81] shows a more extensive set of nanoclusters and see also ref [88] for high level DFT results on electron-hole localisation in TiO2 nanoclusters, showing consistency between the different DFT approaches and models.…”
Section: Tio2 Nanocluster Modified Rutile Tio2 As a Model System For mentioning
confidence: 99%
“…It may be supported by polaronic lattice deformations that act as precursors for self-trapped electron (STE) and self-trapped hole (STH) type polaronic charges. 35 Next we explain the main parameters of the electronic structure of Ga 2 O 3 in Figs. 5 and 6.…”
Section: A Atomic Model Of Intrinsic Defect Statesmentioning
confidence: 99%